Ocular Melanoma Metastasizing to Intra-Abdominal Lymph Nodes - David Aranovich; Karen Meir; Michal M. Lotem; Liat Appelbaum; Hadar Merhav (Case Reports in Surgery)
Background. Visceral metastatic spread of ocular melanoma most commonly occurs via hematogenous route to the liver. Lymphatic spread of ocular melanoma into abdominal lymph nodes has not been reported previously. Case Presentation. A 47-year-old man with a history of ocular melanoma presented with a soft tissue mass on CT scan. The mass encased the portal structures of the hepaticoduodenal ligament. Image-guided biopsy revealed it to be a metastatic melanoma to lymph nodes. The patient underwent surgery with the intent to prolong disease-free survival. On final pathological examination, two lymph nodes were found harboring metastatic melanoma. Conclusion. Extrahepatic lymphatic intra-abdominal spread of ocular melanoma is not impossible. Since this mode of spread is rare, the oncologic significance of surgical resection of isolated intra-abdominal nodal with metastatic ocular melanoma is difficult to determine at the present time.